Cardiac disorders with psychosomatic background - Bielejewska, Ada; Bociek, Arkadiusz; Ślusarczyk, Rafał; Sadowski, Marcin (Medical Studies/Studia Medyczne, 2017)
Psychosomatic disorders can be described as psychosocial-derived organic disorders. The influence of depression, sleep disorders, quality of life, addictions, work environment, family situation, and stress on atrial fibrillation, palpitations, syncope, chest pain, coronary heart disease, and heart failure has been analysed in this paper. The correlation between psychosomatic disorders and the cardiovascular system has been shown. It allows us to conclude that an attending physician, while taking medical history of cardiac patients, should take into consideration factors that may have a negative impact on their mental health, which can be risk factors in the development or aggravation of an already present cardiovascular disease.